Fardhu Kifayah Learning Media Application Using Android-Based Augmented Reality - Baratih, Ira Iranda Isyha; Fakhriza, M. (Ali Institute of Research and Publication, 2025)
Advances in information technology and telecommunications have brought significant changes to the field of education. Technology-based learning media provides an effective solution for improving the quality of learning and student motivation. One of the emerging technologies is augmented reality (AR), which can create interactive and engaging learning experiences. Observations at the Amal Shaleh Islamic Junior High School revealed the need for more interactive, technology-based learning tools. The learning process still relies on conventional methods, such as explanations on the blackboard and textbooks, making it challenging for students to fully grasp the material. The researchers chose the topic